Dietary quality varies according to data collection instrument: a comparison between a food frequency questionnaire and 24-hour recall - Paulo Rogério Melo Rodrigues; Rita Adriana Gomes de Souza; Mara Lima De Cnop; Luana Silva Monteiro; Camila Pinheiro Coura; Alessandra Page Brito; Rosangela Alves Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract The objective of this study was to assess the agreement between the Brazilian Healthy Eating Index - Revised (BHEI-R), estimated by a food frequency questionnaire (FFQ) and multiple 24-hour recalls (24h-R). The Wilcoxon paired test, partial correlations (PC), intraclass correlation coefficient (ICC), and Bland-Altman method were used. The total BHEI-R scores and its components ("total fruits", "whole fruits", "total vegetables", "integral cereals", "saturated fat", "sodium", and "energy intake derived from solid fat, added sugar, and alcoholic beverages") were statistically different, with the ICC and PC indicating poor concordance and correlation. The mean concordance estimated for the total BHEI-R and its components varied from 68% for "integral cereals" to 147% for "whole fruits". The suitable concordance limits were violated for most of the components of the BHEI-R. Poor concordance was observed between the BHEI-R estimated by the FFQ and by multiple 24h-R, which indicated a strong reliability of the BHEI-R on the instrument used to collect information on food consumption.